Supervisor support, work/family conflict and employee satisfaction among nurses in health care service - Wan Rashid, Wan Edura; Nordin, Mohamad Sahari; Omar, Azura; Ismail, Izhairi (2012)
Understanding work and family roles is critically important for organization in enabling employee to experience satisfaction in life. Besides, this is one of the possible solutions for organization to attract and retain capable employee. The present study aims to validate the hypothesized interrelationships among the constructs of supervisor support, work-family conflict and satisfaction outcomes among nurses. Survey questionnaire was administered to 689 married nurses employed in five regional public hospitals in Malaysia. The hypothesized relationships were tested using a full structural modeling with AMOS maximum likelihood estimation. The results indicated that supervisor support is positively related to satisfaction of employee such as well-being, family and job satisfaction. However, the findings also revealed that supervisor support is negatively related to work-family conflict and satisfaction outcomes. The research concluded that the need of supervisor support is practically important in helping employee to achieve satisfaction in life.